Pelayanan Pastoral Bagi Suku Menangki Di Tengah Harapan Hidup Pasca Konflik Di Jemaat GKI Diaspora Skopro Arso Timur : Pastoral Service for the Menangki Tribe in the Midst of Post-Conflict Life Expectancy in the GKI Diaspora Congregation of Skopro Arso Timur - Waimuri, Amelia (MURAI: Jurnal Papua Teologi Konstekstual, 2025)
This research aims to be able to answer the question, how is the form and meaning of pastoral care for the marginalized Menangki tribe in the midst of post-conflict life expectations? The focus of the research is directed at the role of the church in pastoring marginalized congregations who live in conditions of trauma, social limitations, and uncertainty due to the conflict they experienced. The main objective of this research is to deeply understand the practice of pastoral care and its impact on the recovery of faith strengthening, and self-actualization of marginalized people in church and community life. The method used is a qualitative approach with a case study research type. Data were obtained through in-depth interviews, participatory observation, and document study of the Kerom Klasis and the GKI Diaspora Skopro congregation that serves the congregation. The results showed that pastoral care can touch the spiritual, emotional, social and cultural aspects, so as to rebuild the life expectancy of marginalized people. Pastoral care is not only a means of spiritual recovery, but also opens space for participation and empowerment in social life. The discussion of this research emphasizes the importance of pastoral theology that sides with those who are excluded, as well as the war of the church as an agent of reconciliation and hope in post-conflict societies.